Multicellular Spheroids Formation on Hydrogel Enhances Osteogenic/Odontogenic Differentiation of Dental Pulp Stem Cells Under Magnetic Nanoparticles Induction - Han X (Dove Medical Press, 2021)
Xiao Han,1,2 Shijia Tang,1 Lin Wang,1 Xueqin Xu,2 Ruhan Yan,2 Sen Yan,3 Zhaobin Guo,4 Ke Hu,1,2 Tingting Yu,5 Mengping Li,2 Yuqin Li,2 Feimin Zhang,1,2 Ning Gu2,3 1Jiangsu Key Laboratory of Oral Diseases, Affiliated Hospital of Stomatology, Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China; 2Laboratory of Oral Regenerative Medicine Technology, School of Biomedical Engineering and Informatics, Department of Biomedical Engineering, Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China; 3Jiangsu Key Laboratory for Biomaterials and Devices, School of Biological Science and Medical Engineering, Southeast University, Nanjing, Jiangsu, People’s Republic of China; 4Institute for Nanobiotechnology, Johns Hopkins University, Baltimore, MD, USA; 5Department of Medical Genetics, School of Basic Medical Science & Jiangsu Key Laboratory of Xenotransplantation, Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of ChinaCorrespondence: Feimin Zhang; Ning Gu Fax +86-25-86516414; +86-25-83272460Email fmzhang@njmu.edu.cn; guning@seu.edu.cnIntroduction: Promotion odontogenic differentiation of dental pulp stem cells (DPSCs) is essential for dentin regeneration. Physical cellular microenvironment is of critical importance for stem cells differentiation and influences the function of other biological/chemical factors to differentiation.Methods: Based on adjusting the mechanical/interfacial properties of hydrogels, multicellular spheroids (MCSs) of DPSCs generated through self-organization. The spheroids were characterized by immunofluorescent staining and flow cytometry. Quantitative real-time polymerase chain reaction, alkaline phosphatase (ALP) activity assay, ALP staining and Alizarin Red S staining were performed to evaluate the osteogenic/odontogenic differentiation of DPSCs with or without magnetic iron oxide nanoparticles (IONPs) induction.Results: MCSs of DPSCs exhibited a significant upregulation of E-cadherin and N-cadherin and enriched CD146 positive subpopulation, along with a stronger osteogenic/odontogenic differentiation ability. Moreover, DPSCs spheroids showed more substantial osteogenic differentiation tendency than the classical two-dimensional cultured DPSCs under the stimulation of magnetic IONPs.Conclusion: Three-dimensional spheroids culture of DPSCs based on composite viscoelastic materials combined with mechanical/magnetic stimulation may provide a theoretical basis for the subsequent development of dentin or bone regeneration technology.Keywords: tunable mechanical properties, dental pulp stem cells, magnetic nanomaterials, osteogenic/odontogenic differentiation, multicellular spheroids